(3JYdjbI dWjaIs - (3TQa GdOjf CHh CjhH ehSi Hf CMeO GdCjhHj GdCfUGQj, ehSi GdCjhHj,J (B1000 (3g` s
(3ChdgG (B:s
(3hHYO agPg JYdjbI dWjaI QGFbI XQjaI JTJed Ydi bUGFO s
(3BNQgG (B:s
(3YOe GdhaG efge deGA Gdfjd s
(3GdhQbJGf (B94s
95 (3JMedGf JQLeI PGJjI ddeDda HNWgs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JYdjb s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs